Penyelesaian Sengketa Tata Usaha Negara: Obyek Sengketa Negatif dan Penerapan Asas-Asas Umum Pemerintahan Yang Baik - Ahmad Rayhan; H.E. Rakhmat Jazuli; Nurikah Nurikah (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
The resolution of state administrative disputes is intricately tied to the procedural law of the state administrative court, employing routes through both judicial and administrative channels. Governed by Laws No. 5 of 1986 and No. 9 of 2004, the State Administrative Court serves the purpose of providing a platform for dispute settlement and protection for the public, rooted in the general principles of good governance. The settlement of state administrative disputes, particularly those arising from negative object disputes, involves addressing unprofessional conduct by state administration officials, as delineated in Article 3 of Law No. 5 of 1986. This conduct, even if not formalized through a decision letter, is deemed a rejection under the said law. The unprofessional conduct, indicative of losses incurred by individuals or legal entities, aligns with the broader principles of good governance. In this context, state administration officials incur losses through violations of obligations that should safeguard the rights of individuals or legal entities. Article 53, paragraph (2) of Law No. 9 of 2004 underscores the importance of filing a lawsuit based on violations of the general principles of good governance. The application of these principles becomes pivotal in handling state administration disputes with negative object disputes, given the absence of a written object of dispute and reliance solely on the unprofessional conduct of state administration bodies or officials, who reject claims without issuing a formal decision. This underscores the significance of examining the procedural law of the state administrative court, where actions of state administrative bodies or officials are scrutinized for potential violations of the law in the absence of formalized government actions.